2019
DOI: 10.1038/s41423-019-0316-z
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 protects conventional human T cells from premature restimulation-induced cell death

Abstract: The adaptive immune response relies on specific apoptotic programs to maintain homeostasis. Conventional effector T cell (Tcon) expansion is constrained by both forkhead box P3 (FOXP3) +-regulatory T cells (Tregs) and restimulation-induced cell death (RICD), a propriocidal apoptosis pathway triggered by repeated stimulation through the T-cell receptor (TCR). Constitutive FOXP3 expression protects Tregs from RICD by suppressing SLAM-associated protein (SAP), a key adaptor protein that amplifies TCR signaling st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Because FOXP3 is expressed in activated expanding T cons when antigen and IL-2 are abundant, we reasoned that transient FOXP3 upregulation may protect activated Tcons from premature RICD by suppressing SAP expression, mirroring its function in Tregs. We showed that siRNA-mediated knockdown of FOXP3 significantly enhanced RICD sensitivity during in vitro clonal expansion of human T cells, a finding not conferred in latestage, terminally differentiated T cells (Voss et al, 2019b). However, FOXP3 silencing did not impact SAP expression, and SAP and NTB-A were not required for residual RICD at this early stage.…”
Section: Relative Ricd Resistance During Clonal Expansionmentioning
confidence: 73%
“…Because FOXP3 is expressed in activated expanding T cons when antigen and IL-2 are abundant, we reasoned that transient FOXP3 upregulation may protect activated Tcons from premature RICD by suppressing SAP expression, mirroring its function in Tregs. We showed that siRNA-mediated knockdown of FOXP3 significantly enhanced RICD sensitivity during in vitro clonal expansion of human T cells, a finding not conferred in latestage, terminally differentiated T cells (Voss et al, 2019b). However, FOXP3 silencing did not impact SAP expression, and SAP and NTB-A were not required for residual RICD at this early stage.…”
Section: Relative Ricd Resistance During Clonal Expansionmentioning
confidence: 73%
“…Several factors govern RICD sensitivity in late-stage effector T cells, but little is known about mechanisms of RICD resistance in early expanding T cells. A recent study from our group showed that early expanding conventional human effector T cells are less susceptible to RICD in part due to the influence of the transcription factor FOXP3 and autophagy 10 . It is also plausible that newly activated T cells avoid RICD via downregulation of TCR/CD3 expression 68 .…”
Section: Discussionmentioning
confidence: 93%
“…A number of mechanisms have been described which sensitize T cells to RICD. We and other groups have shown that the cell cycle phase 4 , IL-2 signaling 5 , metabolic state 6,7 , SAP and natural killer (NK), T, B cell antigen (NTB-A) expression 8 , diacylglycerol kinase alpha (DGKα) activity 9 , and transient expression of transcription factors such as forkhead box protein 3 (FOXP3) 10 can all influence when and how conventional T cells are susceptible to RICD. One key driver of differential RICD sensitivity in late-stage effector T cells is relative TCR signal strength 11 ; only T cells that reach a critical TCR signal threshold via strong, repeated restimulation will succumb to RICD.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these data suggest that the FOXP3 deficiency has different impacts on T cell function in variously polarized Th cells. More recently, FOXP3 has been shown to play a role in preventing activation‐induced cell death in conventional T cells 74 …”
Section: Immune Dysregulation and Role Of Foxp3 Outside Of The Treg C...mentioning
confidence: 99%